Optimalisasi Arus Lalu Lintas Melalui Fasilitas U-Turn Di Persimpangan Jalan G. Obos XII Kota Palangka Raya - Rika Rika (INFO-TEKNIK, 2026)
U-Turn in front of the Darussalam Grand Mosque, Palangka Raya City, Central Kalimantan Province, is an arterial road with a relatively high traffic volume. The road is equipped with a median and 14 U-Turns. Observations show that vehicles often face delays or queues and have to perform additional maneuvers to complete the U-Turn movement smoothly, leading to disruptions in safety and driving comfort. The purpose of this study is to determine the performance of U-Turn on traffic flow and capacity using the 2023 Indonesian Road Capacity Guidelines (PKJI), the 2005 U-Turn Planning Guidelines, and simulations with PTV Vissim Software. The results showed that the degree of saturation (Dj) was 0.44 in the direction of the Small Roundabout and 0.58 in the direction of Mahir Mahar. The average travel time for the latest U-Turn is 12.64 seconds to the Small Roundabout (queue 28 meters) and 6.66 seconds to Mahir Mahar (queue length of 36 meters). The recommendation proposes a change of location by closing U-Turn point 1, so that the total distance of the U-Turn is 645 m, which is predicted to reduce the queue length to 10.5 meters (in the direction of the Small Roundabout) and 10.4 meters (in the direction of Mahir Mahar).